2018
DOI: 10.3389/fphar.2018.00234
|View full text |Cite
|
Sign up to set email alerts
|

Qianlie Xiaozheng Decoction Induces Autophagy in Human Prostate Cancer Cells via Inhibition of the Akt/mTOR Pathway

Abstract: Qianlie Xiaozheng decoction (QLXZD), a traditional Chinese medicinal formula, has been used clinically to treat advanced prostate cancer (PCa) for more than 10 years. However, experimental evidence supporting its efficacy is lacking. Here, we investigated the anticancer properties and molecular mechanism of QLXZD in vitro in a human PCa cell line (PC3) and in vivo using PC3 xenografts in nude mice. We confirmed the antineoplastic activity of QLXZD by analyzing cell viability and tumor volume growth, which decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Several clinical trials on patients with metastatic colorectal cancer have shown that chloroquine and HCQ are useful only when they are combined with chemotherapeutic agents, inhibitors of histone deacetylases and antiangiogenic agents 45,46. Inhibition of autophagy with molecules such as HCQ and 3-MA is identified by the accumulation of p62 and LC3B in CRC cell lines 47,48. Furthermore, 3-MA inhibits the first steps of autophagy and seems to reduce the protein levels of Beclin-1 in 3 out of 4 used MSS CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials on patients with metastatic colorectal cancer have shown that chloroquine and HCQ are useful only when they are combined with chemotherapeutic agents, inhibitors of histone deacetylases and antiangiogenic agents 45,46. Inhibition of autophagy with molecules such as HCQ and 3-MA is identified by the accumulation of p62 and LC3B in CRC cell lines 47,48. Furthermore, 3-MA inhibits the first steps of autophagy and seems to reduce the protein levels of Beclin-1 in 3 out of 4 used MSS CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that TAIII induces the expression of the autophagy-associated proteins Beclin 1 and LC3-II, while reducing the proliferation of Jurkat cells in vitro. There have been a substantial amount of studies indicating that PI3K/Akt/mTOR signaling are key axes involved in anticancer drug-induced autophagy (8,34,35). Further investigation was performed, with a conclusion that the PI3K/Akt/mTOR signaling pathway was inactivated by TAIII through suppressing the expression of p-PI3K, p-Akt and p-mTOR.…”
Section: Discussionmentioning
confidence: 99%
“…Qianlie Xiaozheng decoction (QLXZD), a polyherbal formulation containing Coix lacryma-jobi and six other herbs, is clinically used to treat prostate cancer. The only mechanistic study on QLXZD to date reported its autophagyrelated toxicity to involve inhibition of the Akt/mTOR pathway [146] in PC3 cells and PC3 xenografts mice.…”
Section: Understudied Herbal Medicines As Potential Candidates For Cancer Metabolomics Studiesmentioning
confidence: 99%